Nanosheet oil-displacing agent as well as preparation and application thereof

By using metal magnesium salts and auxiliary agents to prepare sheet-like magnesium hydroxide nanomaterials under low-cost conditions and undergoing silane coupling modification, the problems of difficulty in injection of oil dampers and low interface contact efficiency in low-permeability reservoirs are solved, and efficient preparation and application of nanosheet oil dampers are achieved.

CN119529801AActive Publication Date: 2025-02-28PETROCHINA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311091765.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-02-28
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the micro-oil cleaning efficiency in low-permeability oil reservoirs, and conventional oil dispersants have problems such as difficulty in injection and low interface contact efficiency.

Method used

A low-cost metal magnesium salt is used as the main raw material, and a sheet-like magnesium hydroxide nanomaterial is prepared by co-precipitation method combined with auxiliary agents, and surface modification is carried out by silane coupling agent to form an amphiphilic sheet-like nanosheet oil repellent.

Benefits of technology

It realizes the preparation of two-dimensional sheet nanomaterials with excellent performance under low-cost conditions, improves the contact efficiency of oil-water interface and reduces interface tension, and enhances the oil-fighting effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529801A_ABST
    Figure CN119529801A_ABST
Patent Text Reader

Abstract

The invention discloses a nanosheet oil-displacing agent and preparation and application thereof.The interfacial tension of the nanosheet oil-displacing agent ranges from 0.27 mN / m to 4.21 mN / m. A preparation method of the nanosheet oil-displacing agent comprises the steps that S1, sodium octadecyl benzene sulfonate is dissolved with methyl alcohol to react with formaldehyde, and an auxiliary agent is obtained; s2, dispersing an auxiliary agent and a magnesium source in deionized water to form a dispersion liquid, adjusting the pH value of the dispersion liquid to be alkalescent, then adding a precipitator for reaction, and performing purification and drying treatment to obtain a flaky magnesium hydroxide nano material; s3, carrying out a reaction on the flaky magnesium hydroxide nano material and 3-aminopropyltriethoxysilane, and carrying out purification and drying treatment, so as to obtain a flaky silane modified magnesium hydroxide nano material; and S4, mixing the flaky silane modified magnesium hydroxide nano material with water, and adding an ampholytic surfactant to obtain the nanosheet oil-displacing agent. The method disclosed by the invention is simple and low in production cost, and the prepared nanosheet oil-displacing agent can effectively reduce the oil-water interfacial tension so as to improve the crude oil recovery rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nanosheet oil-displacing agent and a preparation method and application thereof. Background Art

[0002] With the increasingly serious energy problems, the development of low-permeability reservoirs has also become the focus of research in the oil field. However, due to the complex pore throat structure, small pore size and large specific surface area of ​​low-permeability reservoirs, conventional oil displacement agents have problems such as difficulty in injection. In addition, the development of natural fractures in the reservoirs causes serious heterogeneity in low-permeability reservoirs, and the remaining oil is difficult to be effectively mobilized, which also makes it difficult for conventional surfactant flooding, polymer flooding and other technologies to produce good development effects in low-permeability reservoirs.

[0003] Nanomaterials not only show good injection ability in the exploitation of low-permeability pores, but also can effectively improve the micro-oil washing efficiency by changing the wettability of the reservoir, reducing interfacial tension, and stripping the interfacial oil film. The oil recovery technology system based on nanomaterials is the key to improving the recovery rate of low-permeability reservoirs and is of great significance to the exploitation of oil and gas.

[0004] Traditional nanomaterial research focuses on one-dimensional spherical nanoparticles (such as SiO2, TiO2, Al2O3, CuO, ZnO, etc.). Spherical nanoparticles usually have advantages such as simpler manufacturing process and lower cost, but they have disadvantages such as easy aggregation and blockage, low contact efficiency with the oil-water interface, small specific surface area, few active sites, and low modification efficiency.

[0005] The two-dimensional sheet-like nanomaterials discovered in the new study have the characteristics of large specific surface area, many active sites, and high contact efficiency with the oil-water interface. However, the sheet-like nanomaterials currently used in nanosheet oil displacement agents are mainly molybdenum disulfide, graphene oxide, etc., and the preparation of such nanomaterials is usually accompanied by complex processes and high costs, lacking industrial value. Summary of the invention

[0006] The present invention is made in order to prepare two-dimensional sheet-like nanomaterials for oil displacement with excellent performance under low cost conditions.

[0007] As a first aspect of the present invention, it relates to a nanosheet oil-displacing agent, wherein the interfacial tension of the nanosheet oil-displacing agent is 0.27 to 4.21 mN / m.

[0008] As a second aspect of the present invention, it relates to a method for preparing the above-mentioned nanosheet oil-displacing agent, characterized in that the method comprises the following steps:

[0009] S1: using methanol to dissolve sodium octadecylbenzenesulfonate and reacting it with formaldehyde to obtain an auxiliary agent;

[0010] S2: dispersing the auxiliary agent and magnesium source prepared in S1 in deionized water to form a dispersion, adjusting the pH value thereof to be weakly alkaline, adding a precipitant to react, and obtaining a flaky magnesium hydroxide nanomaterial after purification and drying;

[0011] S3: reacting the flaky magnesium hydroxide nanomaterial prepared in S2 with 3-aminopropyltriethoxysilane, and obtaining a flaky silane-modified magnesium hydroxide nanomaterial after purification and drying;

[0012] S4: mixing the flaky silane-modified magnesium hydroxide nanomaterial prepared in S3 with water, and adding an amphoteric surfactant to obtain a nanosheet oil displacement agent.

[0013] Furthermore, the auxiliary agent has the following structural formula:

[0014]

[0015] Furthermore, the S1 specifically includes the following steps:

[0016] S11: placing sodium octadecylbenzenesulfonate in a reaction container, and then adding methanol as a solvent;

[0017] S12: at a reflux temperature of 65 to 75° C., stirring at a speed of 300 to 500 r / min, adding formaldehyde dropwise to the reaction container at a speed of 2 to 3 mL / min for reaction;

[0018] S13: After the reaction is completed, the solvent is removed by reduced pressure distillation and vacuum drying to obtain an auxiliary agent.

[0019] Furthermore, the molar mass ratio of sodium octadecylbenzenesulfonate to formaldehyde in S11 is 1.0:2.0-3.0.

[0020] Furthermore, the S2 specifically includes the following steps:

[0021] S21: adding the auxiliary agent and the magnesium source to deionized water in a mass ratio of 1.0:1.0-8.0 to form a monomer solution, stirring the solution under the assistance of ultrasonic vibration to form a dispersion, and adjusting the pH value of the dispersion to 9-11 with an alkaline substance;

[0022] S22: stirring the dispersion in S21 at 20 to 95° C. at a speed of 200 to 600 r / min to obtain a suspension; and adding a precipitant dropwise during the stirring process to obtain a suspension;

[0023] S23: The suspension in S22 is stirred and reacted at 20-95° C. for more than 30-300 minutes, and then purified and dried to obtain a flaky magnesium hydroxide nanomaterial.

[0024] Furthermore, the magnesium source in S21 is at least one of magnesium chloride or magnesium nitrate.

[0025] Furthermore, the alkaline substance in S21 is at least one of sodium hydroxide or ammonia water.

[0026] Furthermore, the precipitant in S22 is at least one of sodium hydroxide or ammonia water.

[0027] Furthermore, the mass ratio of the precipitant to the auxiliary agent in S22 is 2.0-6.0:1.0.

[0028] Furthermore, the S3 specifically includes the following steps:

[0029] S31: adding the flaky magnesium hydroxide nanomaterial into anhydrous ethanol, and stirring the flaky magnesium hydroxide nanomaterial under the assistance of ultrasonic vibration to form a dispersion;

[0030] S32: Stir the dispersion in S31 at 30-50° C. and at a speed of 400-600 r / min to uniformly obtain a suspension; dropwise add 3-aminopropyltriethoxysilane during the stirring process; and continue stirring and reacting for 16-30 hours after the dropwise addition is completed to obtain a suspension;

[0031] S33: purifying and drying the suspension obtained in S32 to obtain flaky silane-modified magnesium hydroxide nanomaterials.

[0032] Furthermore, the mass ratio of 3-aminopropyltriethoxysilane to flaky magnesium hydroxide nanomaterial in S32 is 0.5-2.0:1.0.

[0033] Furthermore, the S4 specifically includes the following steps:

[0034] S41: mixing the flaky silane-modified magnesium hydroxide nanomaterial prepared in S3 with water in a mass ratio of 1.0 to 5.0:1000, and then ultrasonically dispersing for 0.5 to 1 hour to obtain a dispersion of the flaky silane-modified magnesium hydroxide nanomaterial;

[0035] S42: uniformly dissolving the amphoteric surfactant in the dispersion of the flaky silane-modified magnesium hydroxide nanomaterial described in S41 to obtain a nano-sheet oil displacement agent.

[0036] Furthermore, the mass ratio of the amphoteric surfactant to water in S42 is 1 to 10:1000.

[0037] Furthermore, the amphoteric surfactant in S42 is one of dodecyl ethoxy sulfobetaine, dodecyl dimethyl hydroxypropyl sulfobetaine, and dodecyl dimethyl sulfopropyl betaine.

[0038] As a third aspect of the present invention, it relates to the application of the above-mentioned nanosheet oil-displacing agent in oil field exploitation.

[0039] The present invention applies an auxiliary agent to prepare magnesium hydroxide by a coprecipitation method, and the auxiliary agent plays the role of a dispersant and a structure directing agent, thereby assisting in controlling the formation of a flaky nano material. When the auxiliary agent is used as a dispersant, it plays a role in enhancing steric hindrance, can prevent the agglomeration of nano materials, and thereby plays a role in controlling the particle size of the magnesium hydroxide nano material; when it is used as a structure directing agent, it has a direct guiding effect on the growth of magnesium hydroxide, and the hydroxyl groups on the auxiliary agent form coordination bonds with magnesium ions, so that the auxiliary agent can be adsorbed on the surface of magnesium hydroxide, and the auxiliary agent can inhibit the longitudinal growth of magnesium hydroxide crystals through the presence of benzene rings and long carbon chains thereon, thereby guiding the formation of magnesium hydroxide flaky morphology, thereby realizing a method for stably preparing flaky magnesium hydroxide nano materials.

[0040] The flaky magnesium hydroxide nanomaterial prepared by the method of the present invention can be modified by coupling with 3-aminopropyltriethoxysilane to become an amphiphilic flaky nanomaterial, which exhibits very good dispersibility in the solution, has the functions of strong interfacial tension reduction, automatic adsorption at the oil-water interface, and can be compounded with a surfactant to form a nano-flaky oil-displacing agent.

[0041] The present invention uses low-cost metal magnesium salt as the main raw material, combines auxiliary agents under a low-energy coprecipitation method to achieve the preparation of flaky magnesium hydroxide nanomaterials, and on this basis, the flaky magnesium hydroxide nanomaterials are surface-modified by a silane coupling agent, and then an amphiphilic flaky oil-displacing agent can be obtained by physical blending. The preparation method of the present invention is simple and stable, and the raw material cost is low. It can stably and efficiently synthesize a flaky magnesium hydroxide nanomaterial with a large specific surface area, multiple active sites, and high oil-water interface contact efficiency under low-cost conditions, thereby forming a low-cost amphiphilic nanosheet oil-displacing system, which has industrial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a SEM image of the flaky magnesium hydroxide nanomaterial prepared in Example 4;

[0043] Figure 2 This is a SEM image of the flaky magnesium hydroxide nanomaterial prepared in Comparative Example 1;

[0044] Figure 3 This is the SEM image of the flaky magnesium hydroxide nanomaterial prepared in Comparative Example 2. DETAILED DESCRIPTION

[0045] The following is a detailed description of the embodiments of the present invention: The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters for which specific conditions are not specified in the following embodiments are generally based on conventional conditions.

[0046] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0047] Example 1

[0048] The steps for preparing the auxiliary agent are as follows:

[0049] Weigh sodium octadecylbenzenesulfonate (4.32 g) and formaldehyde (0.6 g) in a molar ratio of 1:2. Place the weighed sodium octadecylbenzenesulfonate in a 250 mL three-necked flask, add 50 mL of methanol as a solvent, and add formaldehyde dropwise at a rate of 300 r / min (drop speed of 2 mL / min) while stirring at a reflux temperature of 65°C, and react for 3 hours. After the reaction is completed, remove the solvent by reduced pressure distillation and vacuum drying to obtain a viscous solid, which is the target product.

[0050] Example 2

[0051] The steps for preparing the auxiliary agent are as follows:

[0052] Weigh sodium octadecylbenzenesulfonate (4.32 g) and formaldehyde (0.75 g) at a molar ratio of 1:2.5. Place the weighed sodium octadecylbenzenesulfonate in a 250 mL three-necked flask, add 50 mL of methanol as a solvent, and add formaldehyde dropwise at a rate of 400 r / min (drop speed of 2.5 mL / min) at a reflux temperature of 70°C while stirring, and react for 3 hours. After the reaction is completed, remove the solvent by reduced pressure distillation and vacuum drying to obtain a viscous solid, which is the target product.

[0053] Example 3

[0054] The steps for preparing the auxiliary agent are as follows:

[0055] Weigh sodium octadecylbenzenesulfonate (4.32 g) and formaldehyde (0.9 g) in a molar ratio of 1:3. Place the weighed sodium octadecylbenzenesulfonate in a 250 mL three-necked flask, add 50 mL of methanol as a solvent, and add formaldehyde dropwise at a rate of 500 r / min (drop speed of 3 mL / min) while stirring at a reflux temperature of 75°C, and react for 3 hours. After the reaction is completed, remove the solvent by reduced pressure distillation and vacuum drying to obtain a viscous solid, which is the target product.

[0056] Example 4

[0057] The steps for preparing magnesium hydroxide nanomaterial are as follows:

[0058] Take a 250ml beaker, add 0.5g of the auxiliary agent prepared in Example 1, 2g MgCl2 and 100ml deionized water into the beaker, and form a dispersion by ultrasonic vibration. Use ammonia water to adjust the pH value of the dispersion to 10. Pour the dispersion after adjusting the pH into a 250ml flask, add 2g of ammonia solution in a 40°C water bath, and stir at a rate of 400r / min. After the addition is completed, a suspension is obtained. The suspension continues to react at a speed of 400r / min and a temperature of 40°C. The reaction is completed after 4 hours. The product is centrifuged, and the product is washed several times with ethanol and then dried to obtain a dry powder product, which is magnesium hydroxide nanomaterial 1.

[0059] The obtained product was photographed using a scanning electron microscope, and its SEM image is as follows: Figure 1 As shown, it is in good flake shape and has a particle size of about 150nm.

[0060] Comparative Example 1

[0061] The steps for preparing magnesium hydroxide nanomaterial are as follows:

[0062] Take a 250ml beaker, add 0.5g sodium octadecylbenzene sulfonate, 2g MgCl2 and 100ml deionized water into the beaker, and form a dispersion by ultrasonic vibration. Use ammonia water to adjust the pH of the dispersion to 10. Pour the pH-adjusted dispersion into a 250ml flask, add 4g of ammonia solution dropwise in a 40°C water bath, and stir at a rate of 400r / min. A suspension is obtained after the addition is completed. The suspension continues to react at a speed of 400r / min and a temperature of 40°C, and the reaction is completed after 4 hours. The product is centrifuged, and the product is washed several times with ethanol and dried to obtain a dry powder product, which is magnesium hydroxide nanomaterial 2.

[0063] The obtained product was photographed using a scanning electron microscope, and its SEM image is as follows: Figure 2 As shown, it is in block form with a particle size of about 200 nm.

[0064] Comparative Example 2

[0065] The steps for preparing flaky magnesium hydroxide nanomaterials are as follows:

[0066] Take a 250ml beaker, add 2gMgCl2 and 100ml deionized water into the beaker, and form a dispersion by ultrasonic vibration. Use ammonia water to adjust the pH of the dispersion to 10. Pour the pH-adjusted dispersion into a 250ml flask, add 4g of ammonia solution in a 40°C water bath, and stir at a rate of 400r / min. A suspension is obtained after the addition is completed. The suspension continues to react at a speed of 400r / min and a temperature of 40°C. The reaction is completed after 4 hours. The product is centrifuged, washed with ethanol several times, and then dried to obtain a dry powder product, which is magnesium hydroxide nanomaterial 3.

[0067] The obtained product was photographed using a scanning electron microscope, and its SEM image is as follows: Figure 3 As shown, it is spherical and has a particle size of about 110 nm.

[0068] Example 5

[0069] The steps for preparing magnesium hydroxide nanomaterial are as follows:

[0070] Take a 250ml beaker, add 0.5g of the auxiliary agent prepared in Example 2, 0.5g of Mg(NO3)2 and 100ml of deionized water into the beaker, and form a dispersion by ultrasonic vibration. Use sodium hydroxide to adjust the pH value of the dispersion to 11. Pour the dispersion after pH adjustment into a 250ml flask, add 1g of sodium hydroxide solution dropwise in a 20°C water bath, and stir at a rate of 200r / min. A suspension is obtained after the addition is completed. The suspension continues to react at a speed of 200r / min and a temperature of 20°C, and the reaction is completed after 0.5 hours. Centrifuge the obtained product, wash the product several times with ethanol and dry it to obtain a dry powder product, which is magnesium hydroxide nanomaterial 4.

[0071] The obtained product was photographed using a scanning electron microscope, showing good flake shape with a particle size of about 230nm.

[0072] Example 6

[0073] The steps for preparing magnesium hydroxide nanomaterial are as follows:

[0074] Take a 250ml beaker, add 0.5g of the auxiliary agent prepared in Example 1, 4g MgCl2 and 100ml deionized water into the beaker, and form a dispersion by ultrasonic vibration. Use sodium hydroxide to adjust the pH value of the dispersion to 9. Pour the dispersion after pH adjustment into a 250ml flask, add 3g of sodium hydroxide solution dropwise in a 95°C water bath, and stir at a rate of 600r / min. After the addition is completed, a suspension is obtained. The suspension continues to react at a speed of 600r / min and a temperature of 95°C, and the reaction is completed after 5 hours. Centrifuge the obtained product, wash the product several times with ethanol and dry it to obtain a dry powder product, which is magnesium hydroxide nanomaterial 5.

[0075] The obtained product was photographed using a scanning electron microscope, showing good flake shape with a particle size of about 170nm.

[0076] Example 7

[0077] The steps for preparing the nanosheet oil displacement agent are as follows:

[0078] Take a 250ml flask, add 1g of the sheet-like magnesium hydroxide nanomaterial 1 prepared in Example 4 and 100ml of anhydrous ethanol to the flask, and form a dispersion by ultrasonic oscillation. Add 0.5g of 3-aminopropyltriethoxysilane solution dropwise in a 30°C water bath, and stir at a rate of 400r / min. After the addition is completed, the solution continues to react at a speed of 400r / min and a temperature of 30°C, and the reaction is completed after 16 hours. The obtained product is centrifuged, and the product is washed several times with ethanol and then dried to obtain a dry powder product. Take 1g of the dry powder product and add it to 1000g of water, ultrasonically disperse for 30min, and obtain a nanomaterial dispersion. The surfactant dodecylethoxysulfobetaine is added to the dispersion according to a ratio of 0.1wt%, and it is evenly dissolved to obtain a nanosheet oil-displacing agent 1.

[0079] Example 8

[0080] The steps for preparing the nanosheet oil displacement agent are as follows:

[0081] Take a 250ml flask, add 1g of the sheet-like magnesium hydroxide nanomaterial 2 prepared in Example 5 and 100ml of anhydrous ethanol to the flask, and form a dispersion by ultrasonic oscillation. Add 1.3g of 3-aminopropyltriethoxysilane solution dropwise in a 40°C water bath, and stir at a rate of 500r / min. After the addition is completed, the solution continues to react at a speed of 600r / min and a temperature of 40°C, and the reaction is completed after 23 hours. The obtained product is centrifuged, and the product is washed several times with ethanol and then dried to obtain a dry powder product. Take 2.5g of the dry powder product and add it to 1000g of water, ultrasonically disperse for 45min, and obtain a nanomaterial dispersion. The surfactant dodecyl dimethyl hydroxypropyl sulfobetaine is added to the dispersion according to a ratio of 0.5wt%, and it is evenly dissolved to obtain a nanosheet oil-displacing agent 2.

[0082] Example 9

[0083] The steps for preparing the nanosheet oil displacement agent are as follows:

[0084] Take a 250ml flask, add 1g of the sheet-like magnesium hydroxide nanomaterial 3 prepared in Example 6 and 100ml of anhydrous ethanol to the flask, and form a dispersion by ultrasonic oscillation. Add 2.0g of 3-aminopropyltriethoxysilane solution dropwise in a 50°C water bath, and stir at a rate of 600r / min. After the addition is completed, the solution continues to react at a speed of 600r / min and a temperature of 50°C, and the reaction is completed after 30 hours. Centrifuge the obtained product, wash the product with ethanol several times and then dry it to obtain a dry powder product. Take 5g of the dry powder product and add it to 1000g of water, ultrasonically disperse for 60min to obtain a nanomaterial dispersion. Add the surfactant dodecyl dimethyl sulfonpropyl betaine to the dispersion according to a ratio of 1wt%, and dissolve it evenly to obtain a nanosheet oil-displacing agent 3.

[0085] Comparative Example 3

[0086] The steps for preparing the nanosheet oil displacement agent are as follows:

[0087] Take a 250ml flask, add 1g of the flaky magnesium hydroxide nanomaterial prepared in Example 4 into 1000g of water, and ultrasonically disperse for 30min to obtain a nanomaterial dispersion. Add the surfactant dodecyl dimethyl sulfonpropyl betaine to the dispersion at a ratio of 0.3wt% and dissolve it evenly to obtain a nanosheet oil displacement agent 4.

[0088] Test Example 1

[0089] The interfacial tension performance of the nanosheet oil-displacing agents prepared in Example 7, Example 8, Example 9 and Comparative Example 3 was tested using an SVT20N interfacial tension meter.

[0090] First, the sample pool is filled with the nanosheet oil displacement agent prepared by Example 7, Example 8, Example 9 and Comparative Example 3, and the nanosheet mass concentration is diluted to an oil displacement agent solution of 0.05wt%, and then a certain volume of crude oil (Daqing Oilfield) is injected into the center of the sample pool with a micro syringe, and the rotation speed is adjusted to 6000rpm. The image acquisition system is used to capture the change relationship of the oil droplet morphology over time, and the oil-water interfacial tension at different times is calculated according to the oil droplet morphology. After the oil-water interface is stable and unchanged, it is the oil-water interfacial tension when the oil droplet is balanced. Refer to the industry standard SYT5370-1999 of "Surface and Interfacial Tension Determination Method". At the same time, the surfactant dodecyl ethoxy sulfobetaine (referred to as betaine 1), dodecyl dimethyl sulfopropyl betaine (referred to as betaine 2), and petroleum sulfonate are respectively prepared as 0.05wt% aqueous solution as the control group. The test results are shown in Table 1.

[0091] Table 1 Interfacial tension test results

[0092]

[0093] From the analysis of Table 1, it can be seen that the nanosheet oil-displacing agent 1 and the nanosheet oil-displacing agent 2 prepared in Example 7 and Example 8 of the present invention can reduce the interfacial tension to 10 -1 The nano oil-displacing agent 4 prepared in comparative example 3 can only reduce the oil-water interfacial tension to 7.29 mN / m. At the same time, the comparative groups of betaine 1, betaine 2 and petroleum sulfonate reduce the oil-water interfacial tension to 3.34 mN / m, 3.41 mN / m and 1.68 mN / m, respectively. The nanosheet oil-displacing agent 1 and nanosheet oil-displacing agent 2 prepared in examples 7 and 8 of the present invention show stronger interfacial activity.

[0094] Test Example 2

[0095] The nanosheet oil displacement agents prepared in Example 7, Example 8, Example 9 and Comparative Example 3 were subjected to an oil displacement experiment test, and the steps are as follows:

[0096] An artificial core (φ2.5×5cm) was used for oil displacement comparison experiments. The core had a porosity of about 25% and a permeability of about 30mD. After saturation with water, it was saturated with crude oil (viscosity 3.5mPa·s, 25℃), and the displacement experiment was performed after aging for 7 days. Water was driven at a rate of 0.1mL / min until the water content reached 98%, and then 0.3PV oil displacement agent solution was injected into the core at a rate of 0.1mL / min, followed by subsequent water drive at a rate of 0.1mL / min until the water content reached 98%. The oil displacement agent increased the recovery rate based on the difference between the final oil recovery rate and the water drive recovery rate. The results of the increase in the recovery rate of crude oil by different oil displacement agents are shown in Table 2.

[0097] Table 2 Test results of enhanced crude oil recovery (mass fraction of oil displacement agent is 0.05wt%)

[0098]

[0099] From the analysis of Table 2, it can be seen that the nanosheet oil-displacing agent 1 and the nanosheet oil-displacing agent 2 prepared in Examples 7 and 8 of the present invention show a higher degree of enhanced oil recovery, indicating that under the same experimental conditions, the nanosheet oil-displacing agent 1 and the nanosheet oil-displacing agent 2 prepared in Examples 7 and 8 of the present invention have better oil displacement performance than betaine 1, betaine 2 and petroleum sulfonate.

[0100] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art. According to all the teachings disclosed, various modifications and replacements can be made to those details, and these changes are all within the protection scope of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.

Claims

1. A nanosheet oil-displacing agent, characterized in that: The interfacial tension of the nanosheet oil-displacing agent is 0.27-4.21 mN / m.

2. The method for preparing the nanosheet oil-displacing agent according to claim 1, characterized in that: The method comprises the following steps: S1: using methanol to dissolve sodium octadecylbenzenesulfonate and reacting it with formaldehyde to obtain an auxiliary agent; S2: dispersing the auxiliary agent and magnesium source prepared in S1 in deionized water to form a dispersion, adjusting the pH value thereof to be weakly alkaline, adding a precipitant to react, and obtaining a flaky magnesium hydroxide nanomaterial after purification and drying; S3: reacting the flaky magnesium hydroxide nanomaterial prepared in S2 with 3-aminopropyltriethoxysilane, and obtaining a flaky silane-modified magnesium hydroxide nanomaterial after purification and drying; S4: mixing the flaky silane-modified magnesium hydroxide nanomaterial prepared in S3 with water, and adding an amphoteric surfactant to obtain a nanosheet oil displacement agent.

3. The method according to claim 2, characterized in that The auxiliary agent has the following structural formula:

4. The method according to claim 2, characterized in that The S1 specifically includes the following steps: S11: placing sodium octadecylbenzenesulfonate in a reaction container, and then adding methanol as a solvent; S12: at a reflux temperature of 65 to 75° C., stirring at a speed of 300 to 500 r / min, adding formaldehyde dropwise to the reaction container at a speed of 2 to 3 mL / min for reaction; S13: After the reaction is completed, the solvent is removed by reduced pressure distillation and vacuum drying to obtain an auxiliary agent.

5. The method according to claim 4, characterized in that The molar mass ratio of sodium octadecylbenzenesulfonate to formaldehyde in the S11 is 1.0:2.0-3.

0.

6. The method according to claim 2, characterized in that The S2 specifically includes the following steps: S21: adding an auxiliary agent and a magnesium source to deionized water at a mass ratio of 1.0:1.0-8.0 to form a monomer solution, stirring the solution under the assistance of ultrasonic vibration to form a dispersion, and adjusting the pH value of the dispersion to 9-11 with an alkaline substance; S22: stirring the dispersion in S21 at 20 to 95° C. at a speed of 200 to 600 r / min to obtain a suspension; and adding a precipitant dropwise during the stirring process to obtain a suspension; S23: The suspension in S22 is stirred and reacted at 20-95° C. for more than 30-300 minutes, and then purified and dried to obtain a flaky magnesium hydroxide nanomaterial.

7. The method according to claim 6, characterized in that The magnesium source in S21 is at least one of magnesium chloride or magnesium nitrate.

8. The method according to claim 6, characterized in that The alkaline substance in S21 is at least one of sodium hydroxide and ammonia water.

9. The method according to claim 6, characterized in that The precipitant in S22 is at least one of sodium hydroxide and ammonia water.

10. The method according to claim 6, characterized in that The mass ratio of the precipitant to the auxiliary agent in S22 is 2.0-6.0:1.

0.

11. The method according to claim 2, characterized in that The S3 specifically includes the following steps: S31: Adding the flaky magnesium hydroxide nanomaterial into anhydrous ethanol and stirring it under the assistance of ultrasonic vibration , The solution is formed into a dispersion; S32: Stir the dispersion in S31 at 70 to 90° C. at a speed of 400 to 600 r / min to uniformly obtain a suspension; add 3-aminopropyltriethoxysilane dropwise during the stirring process; and continue stirring and reacting for 16 to 30 hours after the addition is completed to obtain a suspension; S33: purifying and drying the suspension obtained in S32 to obtain flaky silane-modified magnesium hydroxide nanomaterials.

12. The method according to claim 11, characterized in that The mass ratio of 3-aminopropyltriethoxysilane to flaky magnesium hydroxide nanomaterial in S32 is 0.5-2.0:1.

0.

13. The method according to claim 2, characterized in that The S4 specifically comprises the following steps: S41: mixing the flaky silane-modified magnesium hydroxide nanomaterial prepared in S3 with water in a mass ratio of 1.0 to 5.0:1000, and then ultrasonically dispersing for 0.5 to 1 hour to obtain a dispersion of the flaky silane-modified magnesium hydroxide nanomaterial; S42: uniformly dissolving the amphoteric surfactant in the dispersion of the flaky silane-modified magnesium hydroxide nanomaterial described in S41 to obtain a nano-sheet oil displacement agent.

14. The method according to claim 13, characterized in that The mass ratio of the amphoteric surfactant to water in the S42 is 0.1 to 1.0:1000.

15. The method according to claim 13, characterized in that The amphoteric surfactant in the S42 is one of dodecyl ethoxy sulfobetaine, dodecyl dimethyl hydroxypropyl sulfobetaine and dodecyl dimethyl sulfopropyl betaine.

16. Use of the nanosheet oil displacement agent according to claim 1 in oil field exploitation.

Citation Information

Patent Citations

  • Using nanoparticles for water flow control in subterranean formations

    CN102037210A

  • Preparation method and application of nitrogen-doped carbon-magnesium composite nano-sheet

    CN108160038A

  • Modified MoS2 nano material and preparation method thereof

    CN109943310A

  • Amphoteric two-dimensional nanosheet as well as preparation method and application thereof

    CN113292978A

  • Amphiphilic nanosheets and methods of making the same

    US20170173546A1